Maximum Torque per Ampere Control of Permanent Magnet Assisted Synchronous Reluctance Motor: An Experimental Study - Yasmine Ihcene Nadjai; Hafiz Ahmed; Noureddine Takorabet; Peyman Haghgooei (Association for Scientific Computing Electronics and Engineering (ASCEE), 2021)
In recent times, permanent magnet assisted synchronous reluctance motors (PMaSRM) have been considered as suitable traction motors for electric vehicle applications. In this type of machine, where the share of reluctance torque is more significant than the excitation torque, it is more appropriate to use a control strategy that can fully utilize the reluctance torque. This paper deals with a new structure of permanent magnet-assisted synchronous reluctance motors that was designed and manufactured in a previous study. This paper suggests applying, in a first study, a constant parameter maximum torque per ampere (MTPA) strategy to make a contribution towards the control of such structure that is becoming increasingly attractive in the field of electric transportation. This method is usually used to control interior permanent magnet synchronous motors to minimize the copper losses of the system. Before implementing and simulating this method, the mathematical models of the suggested motor and the inverter are given. An experimental study is conducted on a small-scale 1 kW prototype PMaSRM using a MicrolabBox Dspace to test and examine the proposed control. Simulation and experimental results are presented in this article in order to verify the validity of the developed control strategy.